Effect of Shade Intensity and Soil Types on the Vegetative Growth and Chlorophyll Content of Javanese Pepper (Piper retrofractum Vahl.) Seedlings - Reo Sambodo; Angki Intan; Wafit Dinarto; Dian Astriani (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Javanese pepper is an indigenous Indonesian spice with high economic value and widely utilized as a traditional medicinal plant. Efforts to increase Javanese pepper production require cultivation optimization, particularly during the nursery stage, which is a key factor in the success of on-farm cultivation. This study aimed to determine the optimal nursery conditions for Javanese pepper in terms of shading intensity and soil type. The study employed a two-factor factorial Randomized Complete Block Design (RCBD). The first factor was shading intensity: N1 = 0%, N2 = 50%, N3 = 70%, and N4 = 90%. The second factor was soil type: T1 = Vertisol, T2 = Regosol, and T3 = Latosol. There were 12 treatment combinations replicated three times, resulting in 36 experimental units. Each unit consisted of five plants, totaling 180 polybags. The selection of soil types was based on the dominant soil distribution in the Special Region of Yogyakarta. Observation data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at the 5% significance level when significant effects were observed. The results showed that the best growth of Javanese pepper seedlings was obtained in Regosol soil under 50–90% shading intensity.